Effect of Hydroxyurea Treatment on the Inflammatory Markers Among Children With Sickle Cell Disease. (14th January 2020) - Zahran, Asmaa M.; Nafady, Asmaa; Saad, Khaled; Hetta, Helal F.; Abdallah, Alam-Eldin M.; Abdel-Aziz, Safwat M.; Embaby, Mostafa M.; Abo Elgheet, Amir M.; Darwish, Sanaa F.; Abo-Elela, Mohamed Gamil M.; Elhoufey, Amira; Elsayh, Khalid I.
Background: Neutrophil-to-lymphocyte ratio (NLR) was introduced as a potential inflammatory marker in sickle cell disease (SCD). This study aimed to evaluate the impact of hydroxyurea (HU) treatment on the value of NLR and some inflammatory mediators in SCD. Methods: The hematological parameters and clinical events were analyzed in 35 children with SCD under HU treatment and followed up for 1 year and in 20 healthy controls. Enzyme-linked immunosorbent assay was performed for the evaluation of proinflammatory cytokines, including interleukin (IL) 6, IL-8, high-sensitivity C-reactive protein (hs-CRP), and tumor necrosis factor α (TNF-α). Results: Hydroxyurea significantly improves most of the hematological parameters in children with SCD. The percentages of hemoglobin fraction S, serum levels of TNF-α and IL-6 were significantly decreased when compared to baseline value but did not reach the value of the healthy control. The HU treatment led to a significant decrease in NLR compared to the baseline values and reached healthy control values. Neutrophil-to-lymphocyte ratio was positively correlated with hs-CRP, TNF-α, and IL-8 serum levels and negatively correlated with percentage of fetal hemoglobin and hematocrit values. The cutoff value of NLR to expect a response to HU among SCD was 3.0, with 76% specificity and 85% sensitivity (area under the curve: 0.85, P < .0001). In conclusion, hydroxyurea induced a decrease in NLR and inflammatory cytokines, which represent a biomarker of inflammation in SCD. The calculation of NLR is a straightforward and cheap method for SCD outcome prediction in young children.